Dynamic changes in mucus thickness and ion secretion during Citrobacter rodentium infection and clearance. - Jenny K Gustafsson; Nazanin Navabi; Ana M Rodriguez-Piñeiro; Ala H A Alomran; Pushpa Premaratne; Harvey R Fernandez; Debashish Banerjee; Henrik Sjövall; Gunnar C Hansson; Sara K Lindén (PLoS ONE, 2013)
Citrobacter rodentium is an attaching and effacing pathogen used as a murine model for enteropathogenic Escherichia coli. The mucus layers are a complex matrix of molecules, and mucus swelling, hydration and permeability are affected by many factors, including ion composition. Here, we used the C. rodentium model to investigate mucus dynamics during infection. By measuring the mucus layer thickness in tissue explants during infection, we demonstrated that the thickness changes dynamically during the course of infection and that its thickest stage coincides with the start of a decrease of bacterial density at day 14 after infection. Although quantitative PCR analysis demonstrated that mucin mRNA increases during early infection, the increased mucus layer thickness late in infection was not explained by increased mRNA levels. Proteomic analysis of mucus did not demonstrate the appearance of additional mucins, but revealed an increased number of proteins involved in defense responses. Ussing chamber-based electrical measurements demonstrated that ion secretion was dynamically altered during the infection phases. Furthermore, the bicarbonate ion channel Bestrophin-2 mRNA nominally increased, whereas the Cftr mRNA decreased during the late infection clearance phase. Microscopy of Muc2 immunostained tissues suggested that the inner striated mucus layer present in the healthy colon was scarce during the time point of most severe infection (10 days post infection), but then expanded, albeit with a less structured appearance, during the expulsion phase. Together with previously published literature, the data implies a model for clearance where a change in secretion allows reformation of the mucus layer, displacing the pathogen to the outer mucus layer, where it is then outcompeted by the returning commensal flora. In conclusion, mucus and ion secretion are dynamically altered during the C. rodentium infection cycle.